2018
DOI: 10.1093/humrep/dey269
|View full text |Cite
|
Sign up to set email alerts
|

Endometriosis and adverse maternal, fetal and neonatal outcomes, a systematic review and meta-analysis

Abstract: STUDY QUESTIONHow is endometriosis associated with adverse maternal, fetal and neonatal outcomes of pregnancy?SUMMARY ANSWERWomen with endometriosis are at elevated risk for serious and important adverse maternal (pre-eclampsia, gestational diabetes, placenta praevia and Cesarean section) and fetal or neonatal outcomes (preterm birth, PPROM, small for gestational age, stillbirth and neonatal death).WHAT IS KNOWN ALREADYA number of studies have shown an association between endometriosis and certain adverse mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
115
6
9

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(149 citation statements)
references
References 48 publications
10
115
6
9
Order By: Relevance
“…There is also evidence that the diagnosis behind infertility on its own can alter the outcome. Endometriosis has been shown to alter perinatal and maternal outcome irrespective of ART or not (Stephansson et al, 2009, Lalani et al, 2018. PCOS, another common reason for infertility treatment, also alters the outcome irrespective of age, BMI or ART (Roos et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…There is also evidence that the diagnosis behind infertility on its own can alter the outcome. Endometriosis has been shown to alter perinatal and maternal outcome irrespective of ART or not (Stephansson et al, 2009, Lalani et al, 2018. PCOS, another common reason for infertility treatment, also alters the outcome irrespective of age, BMI or ART (Roos et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Our results are also consistent with the report that activated platelets activate NF-κB in cancer cells 60 . The resultant hypercoagulability in women with endometriosis 61,62 may be responsible for increased risk of preeclampsia 63,64 due to inflammasome activation in trophoblasts induced by maternal extracellular vesicles and platelets 65 .…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17] It was reported that patients with endometriosis have a significant higher incidence of HDP than those without endometriosis. 18 Another study reported that women with irregular menstrual cycles and dysmenorrhea are more prone to HDP. 19 Although it was not statistically significant, Groups II and IV showed higher incidence of HDP, being compatible with the above previous reports.…”
Section: Discussionmentioning
confidence: 99%